2020
DOI: 10.1080/03075079.2020.1723533
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the number of scientific publications and citations when attaining the rank of professor in Sweden

Abstract: The proportion of women tends to decrease the higher the academic rank, following a global pattern. Sweden has taken comprehensive measures to decrease this gap across 30 years, and many countries are following a similar path. Yet today only 27% of faculty with the rank of professor in Sweden are female. A common explanation is that academia is biased against women. According to this hypothesis, women have to reach higher levels of scholarly achievement than men to be appointed to the same academic rank. Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 50 publications
2
44
1
Order By: Relevance
“…Research productivity is often measured through publications, especially in reputable, peer reviewed journals [ 12 : 84, 13 : 473, 14 : 2]. This is also the case in political science, where “virtually all institutions value peer-reviewed publications over non-peer-reviewed publications, and more over fewer” [ 15 : 510, 513, 16 : 99, 17 : 105, 18 : 185].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research productivity is often measured through publications, especially in reputable, peer reviewed journals [ 12 : 84, 13 : 473, 14 : 2]. This is also the case in political science, where “virtually all institutions value peer-reviewed publications over non-peer-reviewed publications, and more over fewer” [ 15 : 510, 513, 16 : 99, 17 : 105, 18 : 185].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of meritocracy is the best method we know to achieve this, and it has served science very well. To not select and promote the most able individuals (regardless of sex, race, and political views) is, therefore, not only unfair to individual academics but potentially damaging to academia and even to society as a whole” [ 14 : 2]. But are women indeed disadvantaged?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our negative findings regarding the academic outcome of gender mainstreaming is of course logically compatible with there being many positive academic effects of gender mainstreaming, such as increased chances for competent female scientists to pursue an academic career. However, an extensive recent study of publication metrics when attaining the rank of professor at the six largest universities in Sweden in the period 2009-2014 found that men had significantly more publications and citations in both medicine and the social sciences, indicating that Swedish academia was not systematically biased against women's research merits when gender mainstreaming was introduced in 2017 [49]. 14 In fact, a case could be made that Sweden had by then already overcompensated for what is widely believed to be earlier discrimination against women in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that males had 64-80% more scientific publications that had attained 42-260% more citations, resulting in a 72-83% larger h-index ([49], p. 13).…”
mentioning
confidence: 95%